Cost Estimation of Structural Components of a Building by considering the Seismic Load on Different Regions. (18th December 2019) - Mubarak, Mubarak; Abdullah, Abdullah; Azmeri, Azmeri; Hayati, Yulia
Abstract : Seismic loads should be considered in the cost estimation process as a consequence of changes in structural dimensions. Seismic loads received by buildings vary from one region to another, which are used as a basis for dimensioning structural components. This paper aims to investigate the potential cost changes of the reinforced concrete (RC) beam and column elements as an implication of variations in seismic load received by a building constructed in different seismic areas. This study was applied to a prototype of the two-story building. The structure analysis performed with dynamic analysis by varying seismic design categories based on eight seismic zones in the observed area. The utilization of a building prototype was applied to three indices of seismic importance factor to represent the building occupancy category. The results of the study explaining the increase in the total cost of the two RC elements are 0.68%, 1.70%, and 1.54%, respectively, for the seismic importance factor indices of 1.00, 1.25, and 1.50. The variations of the costs due to the factor of seismic load and building occupancy categories indicate that both factors need to be considered in the cost estimation process of buildings.